Protocol to decellularize porcine right ventricular outflow tracts using a 3D printed flow chamber - Amy G. Harris; Vico Schot; Michele Carrabba; Dominga Iacobazzi; Mohamed T. Ghorbel; James P.K. Armstrong; Adam W. Perriman; Massimo Caputo; Giovanni Biglino; Francesca Bartoli-Leonard (STAR Protocols, 2024)
Summary: Surgical treatment of pediatric congenital heart disease with tissue grafts is a lifesaving intervention. Decellularization to reduce immunogenicity of tissue grafts is an increasingly popular alternative to glutaraldehyde fixation. Here, we present a protocol to decellularize porcine right ventricular outflow tracts using a 3D printed flow chamber. We describe steps for 3D printing the flow rig, preparing porcine tissue, and using the flow rig to utilize shear forces for decellularization. We then detail procedures for characterizing the acellular scaffold.For complete details on the use and execution of this protocol, please refer to Vafaee et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.